Inverse calibration matrix algorithm for radiation detection portal monitors. (February 2019) - Kim, Yewon; Kim, Myungsoo; Lim, Kyung Taek; Kim, Jongbum; Cho, Gyuseong
Abstract: Radioisotope identification of an energy spectrum obtained from a radiation portal monitor (RPM) is a challenging task due to its insufficient data acquisition time. Thus, conventional algorithms for a radiation portal monitor, such as the gross count algorithm and the energy window algorithm, use the gross count of the measured spectrum or the gross counts of specific energy ranges. However, the conventional algorithms cause false alarms because they simply compare the gross count of the measured spectrum to the background radiation count. In this paper, an inverse calibration matrix (ICM) algorithm for radioisotope identification is proposed, which uses approaches different from those of conventional algorithms. To evaluate this method, various gamma energy spectra of 133 Ba, 137 Cs, 60 Co, 22 Na, background radiation and a potassium fertilizer that included 40 K were measured by four photomultipliers attached to a large-area polyvinyl-toluene (PVT) scintillator for a radiation portal monitor. The results demonstrated that the energy spectra obtained with measurement times ranging from 0.1 to 50 s were precisely identified by the ICM algorithm. Highlights: Inverse calibration matrix (ICM) algorithm for has been developed. Gamma energy spectra of various radioisotopes were measured. ICM algorithm is able to identify radioisotopes from measured energy spectra.